Bellewether - Kearsley, Susanna, 1966- (Sourcebooks Landmark, 2018)
As war is raging, young French Canadian lieutenant Jean-Philippe de Sabran is captured and billeted with a Long Island family, becoming an unwilling and unwelcome guest who soon has feelings for the daughter of the house, Lydia Wilde.